Blind subjects process auditory spectral cues more efficiently than sighted individuals - Doucet, M.-E.; Guillemot, J.-P.; Lassonde, M.; Gagn, J.-P.; Leclerc, C.; Lepore, F. (Experimental brain research, 2005)
The goal of the present study was to investigate how monaural sound localization on the horizontal plane in blind humans is affected by manipulating spectral cues. As reported in a previous study (Lessard et al. 1998), blind subjects are able to calibrate their auditory space despite their congenital lack of vision. Moreover, the performance level of half of the blind subjects was superior to that of sighted subjects under monaural listening conditions. Here, we first tested ten blind subjects and five controls in free-field (1) binaural and (2) monaural sound localization tasks. Results showed that, contrary to controls and half the blind subjects, five of the blind listeners were able to localize the sounds with one ear blocked. The blind subjects who showed good monaural localization performances were then re-tested in three additional monaural tasks, but we manipulated their ability to use spectral cues to carry out their discrimination. These subjects thus localized these same sounds: (3) with acoustical paste on the pinna, (4) with high-pass sounds and unobstructed pinna and (5) with low-pass sounds and unobstructed pinna. A significant increase in localization errors was observed when their ability to use spectral cues was altered. We conclude that one of the reasons why some blind subjects show supra-normal performances might be that they more effectively utilize auditory spectral cues.